Konsep Komunikasi Pariwisata Berkelanjutan Berbasis Kearifan Lokal di Situs Megalit Tinggihari 1 Kabupaten Lahat - Ariyani, Sherin; Desy Misnawati; Bastian Jabir; Siti Rahayu Lexi Ningrum (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The purpose of this research is to analyze the concept of tourism communication based on local wisdom at Megalithic Site Tinggihari 1, Lahat Regency. Local wisdom is a valuable asset in the development of sustainable tourism, especially in areas with cultural heritage and historical sites like Megalithic Site Tinggihari 1. The theory used is based on Weaver and Lawton's (2010) theory of participatory communication. This research employs a qualitative approach and a case study method to explore various aspects of tourism communication involving local wisdom at this site. Data collection methods include observation, interviews, and the review of documentation related to local wisdom communication in the Lahat Regency Government. Research informants include the local community, Megalithic Site Tinggihari 1 officials, the Lahat Regency Tourism Office, and cultural figures. The results of the research indicate that participatory communication, in the context of tourism communication based on local wisdom at Megalithic Site Tinggihari 1, plays a crucial role in maintaining tourism sustainability and preserving local culture. Through the involvement of the local community, site management, and tourists, messages of local wisdom are conveyed in an informative and educational manner. This communication includes the use of local symbols, folklore, and local wisdom practices to enhance understanding and appreciation of this megalithic site.